Salmonellosis in Peru and the secondary complication of human bartonellosis or Carrion's disease - Colichón Arbulú, Héctor (1958)
In the course of human bartonellosis, native Peru infectious disease and Bartonella bacilliformis producidad by, there is a special state of lower resistance to Salmonella of animal origin in these patients results in severe secondary paratyphosis.